A Multimodal, Nonpharmacologic Intervention Improves Mood and Cognitive Function in People with Multiple Sclerosis. (3rd April 2017) - Lee, Jennifer E.; Bisht, Babita; Hall, Michael J.; Rubenstein, Linda M.; Louison, Rebecca; Klein, Danielle T.; Wahls, Terry L.
ABSTRACT: Objective : The objective of this study was to examine whether participation in a 12-month multimodal intervention would improve mood and cognitive function in adults with progressive multiple sclerosis (MS). Methods : In this one-arm, open-label feasibility trial, participants were prescribed a home-based multimodal intervention, including (1) a modified Paleolithic diet; (2) an exercise program (stretching and strengthening of the trunk and lower limb muscles); (3) neuromuscular electrical stimulation (EStim) of trunk and lower limb muscles; and (4) stress management (meditation and self-massage). Individuals completed measures of mood (Beck Anxiety and Depression Inventories) and cognitive (Cognitive Stability Index, Cognitive Screening Test, Delis–Kaplan Executive Function System) and executive function (Wechsler Adult Intelligence Scale) at baseline and 3, 6, 9, and 12 months after the start of the intervention. Dosage of the multimodal intervention was assessed at 3, 6, 9, and 12 months. Results : The more individuals participated in the intervention activities, the greater improvements they had from baseline to 12 months on self-report measures of anxiety (Beck Anxiety Inventory [BAI]; p s = 0.001 to 0.02), depression (Beck Depression Inventory [BDI]; p s = <0.0001 to 0.09), cognitive function (Cognitive Stability Index [CSI/T], Delis-Kaplan Executive Function System [DKEFS]; p s = 0.001 to 0.06), and executive function (Wechsler Adult Intelligence Scale [WAIS]; p s = <0.0001 to 0.09). Mood and cognitive improvements were more closely related to a higher intake of the modified Paleolithic diet than to exercise and stress management dosage. Anxiety and depression changes were evident after just a few months, whereas changes in cognitive function were generally not observed until later in the intervention period. Mood and cognitive function changes from baseline to 12 months were significantly associated with fatigue improvements ( p s = <0.0001 to 0.03). Conclusions : A modified Paleolithic diet, exercise, EStim, and stress management intervention like this one has the potential to improve the mood and cognitive symptoms that can lead to considerable suffering in people with MS, potentially improving quality of life and function for people with progressive MS.